2023
DOI: 10.3390/ijgi12030120
|View full text |Cite
|
Sign up to set email alerts
|

Filling in the Spaces: Compactifying Cities towards Accessibility and Active Transport

Abstract: Compactification of cities, i.e., the opposite of urban sprawl, has been increasingly presented in the literature as a possible solution to reduce the carbon footprint and promote the sustainability of current urban environments. Compact environments have higher concentrations of interaction opportunities, smaller distances to them, and the potential for increased active mode shares, leading to less transport-related energy consumption and associated emissions. This article presents a GIS-based quantitative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 133 publications
0
13
0
Order By: Relevance
“…Reducing fuel consumption and associated emissions is possible by focusing on three main areas: fuel type, fuel efficiency, and vehicle miles traveled [75][76][77]. While the first two areas are not directly related to the built environment, the latter is, as research shows that land use and urban design policies can help reduce motorized modal share and transport energy consumption in the urban environment [78][79][80][81]. The high modal share of private motorized transport is one of the main causes of high transport energy consumption in cities [82].…”
Section: Transport and The Built Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Reducing fuel consumption and associated emissions is possible by focusing on three main areas: fuel type, fuel efficiency, and vehicle miles traveled [75][76][77]. While the first two areas are not directly related to the built environment, the latter is, as research shows that land use and urban design policies can help reduce motorized modal share and transport energy consumption in the urban environment [78][79][80][81]. The high modal share of private motorized transport is one of the main causes of high transport energy consumption in cities [82].…”
Section: Transport and The Built Environmentmentioning
confidence: 99%
“…Other consequences are an increase in both air and noise pollution, a significant reduction in public transport ridership, and negative socio-economic consequences [163,[165][166][167][168][169]. Studies [79,170] showed the clear effects of residential location on traveling distances, modal share, and transport energy consumption. Dwellers of sprawled suburbs have the worst accessibility and are restricted to motorized transport modes, as walking or cycling is not possible with homes being so distant from destinations.…”
Section: Urban Sprawlmentioning
confidence: 99%
See 3 more Smart Citations